(untitled) (Avaliação: Revista da Avaliação da Educação Superior, 2011)
The main objective of this study is to verify on what sort of evaluation the eighteen advisors of the physical education and sport’s of monographs in Portugal base their judgement when evaluating students. An anonymous and confidential questionnaire was used to verify how their evaluation is processed. Only 38,9% of the advisors explain to their advisees the criteria, parameters, types and objectives of the evaluation that are used in their evaluations. In relation to the formative evaluation, generally, the advisors, in every meeting, take their own conclusions in relation to future classifications, having to do constant feedbacks through a continuous evaluating system. Most of the advisors believe that they would be able to do a much better evaluation if they had more time to spend with their advisees. Finally, 66,7% of the supervisors believe that all the teaching courses should give higher value to the formation in the area of evaluation because it is important to know how to evaluate correctly, so as to be fairer with their students and to learn new evaluation strategies and instruments. The remaining advisors believe that there aren’t enough subjects that actually train the future teachers, in their formation, how to evaluate their students.